Targeting SMYD2 promotes ferroptosis and impacts the progression of pancreatic cancer through the c-Myc/NCOA4 axis-mediated ferritinophagy - Tan, Juan; Liao, Shan; Yuan, Bowen; Liu, Xinrong; Yu, Wentao; Zhan, Han; Jiang, Yan; Liu, Yang (Biochimica et biophysica acta. General subjects, 2024)
Pancreatic cancer (PC) is characterized by a poor prognosis and limited treatment options. Ferroptosis plays an important role in cancer, SET and MYND domain-containing protein 2 (SMYD2) is widely expressed in various cancers. However, the role of SMYD2 in regulating ferroptosis in PC remains unexplored. This study aimed to investigate the role of SMYD2 in mediating ferroptosis and its mechanistic implications in PC progression. The levels of SMYD2, c-Myc, and NCOA4 were assessed in PC tissues, and peritumoral tissues. SMYD2 expression was further analyzed in human PC cell lines. In BxPC3 cells, the expression of c-Myc, NCOA4, autophagy-related proteins, and mitochondrial morphology, was evaluated following transfection with si-SMYD2 and treatment with autophagy inhibitors and ferroptosis inhibitors. Ferroptosis levels were quantified using flow cytometry and ELISA assays. RNA immunoprecipitation was conducted to elucidate the interaction between c-Myc and NCOA4 mRNA. A xenograft mouse model was constructed to validate the impact of SMYD2 knockdown on PC growth. SMYD2 and c-Myc were found to be highly expressed in PC tissues, while NCOA4 showed reduced expression. Among the PC cell lines studied, BxPC3 cells exhibited the highest SMYD2 expression. SMYD2 knockdown led to decreased c-Myc levels, increased NCOA4 expression, reduced autophagy-related protein expression, mitochondrial shrinkage, and heightened ferroptosis levels. Additionally, an interaction between c-Myc and NCOA4 was identified. In vivo, SMYD2 knockdown inhibited tumor growth. Targeting SMYD2 inhibits PC progression by promoting ferritinophagy-dependent ferroptosis through the c-Myc/NCOA4 axis. These findings provide insights into potential diagnostic and therapeutic strategies for PC. [Display omitted] •High levels of SMYD2 are observed in PC tissue and cells.•Knockdown of SMYD2 promotes ferritinophagy-dependent ferroptosis in PC cells.•The impact of SMYD2 knockdown on the c-Myc/NCOA4 axis.•SMYD2 influences PC cell ferritinophagy-dependent ferroptosis via the c-Myc/NCOA4 axis.•Knockdown of SMYD2 inhibits tumor growth through the c-Myc/NCOA4 pathway.